2003
DOI: 10.2337/diacare.26.9.2622
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Plasma Interleukin-18 Concentrations to Hyperhomocysteinemia and Carotid Intimal-Media Wall Thickness in Patients With Type 2 Diabetes

Abstract: OBJECTIVE -We compared plasma interleukin (IL)-18 concentrations in patients with type 2 diabetes with those in age-matched control subjects and investigated whether plasma IL-18 was associated with plasma total homocysteine (tHcy) concentration or carotid intimalmedia wall thickness (IMT), an early marker of atherosclerosis, in these patients.RESEARCH DESIGN AND METHODS -We measured plasma IL-18 in 103 type 2 diabetic patients and 45 age-matched control subjects. We also measured patients' plasma tHcy and ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
70
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 38 publications
13
70
1
1
Order By: Relevance
“…6 Increased IL-18 levels were found in obesity, 7 polycystic ovary syndrome, 8 metabolic syndrome 9 and type 2 diabetes. [10][11][12] Elevated IL-18 concentration was also found to be an independent predictor of the development of type 2 diabetes. 13 In line with the above findings, recent studies provided an evidence that IL-18 is directly associated with insulin resistance.…”
Section: Introductionmentioning
confidence: 98%
“…6 Increased IL-18 levels were found in obesity, 7 polycystic ovary syndrome, 8 metabolic syndrome 9 and type 2 diabetes. [10][11][12] Elevated IL-18 concentration was also found to be an independent predictor of the development of type 2 diabetes. 13 In line with the above findings, recent studies provided an evidence that IL-18 is directly associated with insulin resistance.…”
Section: Introductionmentioning
confidence: 98%
“…Elevated IL-18 levels are found to be associated with increased adiposity and insulin resistance in obese premenopausal women (18,19). IL-18 concentrations are increased in acute hyperglycemia (20) and type 2 diabetes (21,22). Moreover, IL-18 may influence vascular remodeling (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we also found that serum IL-18 levels were positively correlated with carotid IMT and baPWV in patients with type 2 diabetes. Several studies have reported that carotid IMT (11,12) and baPWV (31) are useful markers for evaluation of atherosclerosis in type 2 diabetes. A clinical study reported that decrease in glomerular filtration rate is linked to atherosclerosis (32).…”
Section: Il-18 Is a Predictor Of Diabetic Nephropathymentioning
confidence: 99%
“…Recently, serum IL-18 levels have been reported elevated in patients with diabetic nephropathy (19). IL-18 is known to lead to production of other proinflammatory cytokines (20), endothelial apoptosis (21), upregulation of ICAM-1 (22), and hyperhomocysteinemia (12). Thus, IL-18 might be an important factor not only in the process of atherosclerosis but also in the development and progression of diabetic nephropathy.…”
mentioning
confidence: 99%
See 1 more Smart Citation